Young's modulus extraction of epitaxial heterostructure AlGaN/GaN for MEMS application. Issue 7 (2nd May 2014) - Ben Amar, Achraf; Faucher, Marc; Brandli, Virginie; Cordier, Yvon; Théron, Didier
<x xml:space="preserve">Abstract</x> This paper presents a Young's modulus extraction method for thin film group III‐nitrides materials such as GaN, AlN, and its ternary AlGaN. The AlGaN/GaN heterostructures are grown by molecular beam epitaxy on Si (111) substrate and designed for MEMS applications. Various cantilevers with a width of 10 µm and lengths going from 100 to 310 µm were fabricated. The Young's moduli are determined using the resonance frequencies measured by laser Doppler vibrometry (LDV). Finite element modeling (FEM) is used to consider the under‐etching of the cantilevers at the anchor. In this study, we find that the Young moduli of GaN and AlN layers are respectively 261 ± 60 GPa and 339 ± 78 GPa that compares well with the results found in the literature for bulk materials.